Practices and risks associated with operation of tie-down lashings in the vehicle transport industry. Issue 12 (1st December 2016) - Fraysse, François; Milanese, Steven; Thewlis, Dominic
Abstract: Load restraint systems in automobile transport utilise tie-down lashings placed over the car's tyres, which are tensioned manually by the operator using a ratchet assembly. This process has been identified as a significant manual handling injury risk. The aim of this study was to gain insight on the current practices associated with tie-down lashings operation, and identify the gaps between current and optimal practice. We approached this with qualitative and quantitative assessments and one numerical simulation to establish: (i) insight into the factors involved in ratcheting; (ii) the required tension to hold the car on the trailer; and (iii) the tension achieved by drivers in practice and associated joint loads. We identified that the method recommended to the drivers was not used in practice. Drivers instead tensioned the straps to the maximum of their capability, leading to over-tensioning and mechanical overload at the shoulder and elbow. We identified the postures and strategies that resulted in the lowest loads on the upper body during ratcheting (using both hands and performing the task with their full body). This research marks the first step towards the development of a training programme aiming at changing practice to reduce injury risks associated with the operation of tie-down lashings in the automobile transport industry. Practitioner Summary: The study investigated current practice associated with the operation of tie-down lashings through qualitative (interviews) and quantitative (biomechanical analysis) methods. Operators tended to systematically over-tension the lashings and consequently overexert, increasing injury risks.